ТЎҚИМАЧИЛИК КОРХОНАЛАРИДА ЛИЗИНГ МУНОСАБАТЛАРИНИНГ РИВОЖЛАНИШ ТЕНДЕНЦИЯЛАРИ (Scientific journal of the Fergana State University, 2023)
The article reveals the trends of leasing market development, common problems of leasing application in textile branch (field) and the ways of their overcome.